A study of responsible and ethical AI chatbot in education - Mo, Jiayun (Nanyang Technological University, 2024)
With the expansion of generative Artificial Intelligence (AI) and the penetration of AI chatbots into every aspect of people’s daily lives, discussions and issues related to AI ethics and responsibility began to arise simultaneously. A large portion of AI users remains ignorant of such ethical discussions, while a significant percentage of developers lack precautionary measures to prevent irresponsible AI behaviours. An increasing number of companies and organisations are taking action to address the issues. The United Nations, the European Union, as well as local organisations like the Personal Data Protection Commission, have all launched frameworks and guidelines aiming to regulate AI in the past few years. However, despite the effort, prominent issues still prevail. Most existing solutions are too general and theoretical; few are narrowed down to examine the specific application scenario of AI chatbots in education, which is arguably the domain with the highest number of chatbot usage. Thus, with the arising concerns and the lack of a satisfying solution, this project aims to develop a comprehensive guideline about AI ethics and responsible AI, which will specifically target undergraduate developers and guide them during their future development of AI chatbots used in education.